2022
DOI: 10.1038/s41598-022-18668-w
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation pathways and the role of social-ecological networks in small-scale fisheries

Abstract: Climate change is expected to have increasing impacts on marine ecosystems which will threaten the livelihoods and wellbeing of millions of people. Drawing on social-ecological network and sociodemographic data collected via face-to-face interviews with 404 small-scale commercial fishers from 9 Galician communities (Spain), we empirically examine the adaptation pathways that fishers follow when they face hypothetical impacts on their fishery resources and test the role of five social-ecological network structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The importance of bonding and communicative social relationships among fellow fishers (Fig. 4A ) for adaptation has been demonstrated in a study of Galician fishery communities in Spain, although it was also shown that social relationships based primarily on mutual trust can actually prevent fishers from adapting [ 96 ]. The mechanism behind the latter is not clear, but it is suggested that, for example, trust-based relationships can stimulate ‘too much’ social cohesion that might lock the actors into a status quo.…”
Section: A Network-centric Perspective On Governing Dynamic and Fast-...mentioning
confidence: 99%
“…The importance of bonding and communicative social relationships among fellow fishers (Fig. 4A ) for adaptation has been demonstrated in a study of Galician fishery communities in Spain, although it was also shown that social relationships based primarily on mutual trust can actually prevent fishers from adapting [ 96 ]. The mechanism behind the latter is not clear, but it is suggested that, for example, trust-based relationships can stimulate ‘too much’ social cohesion that might lock the actors into a status quo.…”
Section: A Network-centric Perspective On Governing Dynamic and Fast-...mentioning
confidence: 99%